Trần Ngọc Bảo

Nếu , với , thì  ....

Lightning Farron
6 tháng 8 2016 lúc 23:00

\(\sqrt{\left(\sqrt{2}-\sqrt{3}\right)^2}-\sqrt{\left(1-\sqrt{3}\right)^2}\)

\(=\sqrt{2}-\sqrt{3}-1-\sqrt{3}\)

\(=\sqrt{2}-1-2\sqrt{3}=a+b\sqrt{2}+c\sqrt{3}\) (*)

Nhìn vào (*) ta dễ dàng thấy

\(-2\sqrt{3}=c\sqrt{3}\rightarrow c=-2\)

\(\sqrt{2}=b\sqrt{2}\rightarrow b=1\)

Và a=-1.Suy ra a+b+c=(-2)+1+(-1)=-2

 

 

Bình luận (0)

Các câu hỏi tương tự
Ngô Công Đức
Xem chi tiết
Ngô Hồng Thuận
Xem chi tiết
Ngô Hồng Thuận
Xem chi tiết
nguyễn thị oanh
Xem chi tiết
Toán 9
Xem chi tiết
nguyễn thị oanh
Xem chi tiết
wary reus
Xem chi tiết
Anh Triêt
Xem chi tiết
Toán 9
Xem chi tiết
Trần Ngọc Bảo
Xem chi tiết